2021
DOI: 10.1093/mnras/stab3486
|View full text |Cite
|
Sign up to set email alerts
|

The viewing angle in AGN SED models: a data-driven analysis

Abstract: The validity of the unified active galactic nuclei (AGN) model has been challenged in the last decade, especially when different types of AGNs are considered to only differ in the viewing angle to the torus. We aim to assess the importance of the viewing angle in classifying different types of Seyfert galaxies in spectral energy distribution (SED) modelling. We retrieve photometric data from publicly available astronomical databases: CDS and NED, to model SEDs with X-CIGALE in a sample of 13 173 Seyfert galaxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 146 publications
0
6
0
Order By: Relevance
“…For example, it allows modeling of the X-ray photometry and has state-of-the-art AGN templates (Yang et al 2020(Yang et al , 2022. Previous literature has explored the best fitting strategies and justified its reliability for modeling AGN SEDs; see, e.g., Ciesla et al (2015), Buat et al (2021), Mountrichas et al (2021b), Ramos Padilla et al (2022). Third, dedicated studies of using CIGALE to fit BQ galaxies are also available; see, e.g., Boselli et al (2016), Aufort et al (2020), Ciesla et al (2021).…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it allows modeling of the X-ray photometry and has state-of-the-art AGN templates (Yang et al 2020(Yang et al , 2022. Previous literature has explored the best fitting strategies and justified its reliability for modeling AGN SEDs; see, e.g., Ciesla et al (2015), Buat et al (2021), Mountrichas et al (2021b), Ramos Padilla et al (2022). Third, dedicated studies of using CIGALE to fit BQ galaxies are also available; see, e.g., Boselli et al (2016), Aufort et al (2020), Ciesla et al (2021).…”
Section: Overviewmentioning
confidence: 99%
“…Buat et al (2021) further showed that the SMC extinction law is largely optimal for polar dust and can return reliable results even if the real polar extinction curve is different from the SMC law. The viewing angle is set to include at least one face-on (type 1 AGN) and one edge-on (type 2 AGN) system, and Ramos Padilla et al (2022) showed that the SED-fitting results are insensitive to the choice of viewing angles as long as both type 1 and type 2 representatives are included.…”
Section: Sed Fitting To Select Agn Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our choice of considering only a few viewing angles close to the average values for Type I and II AGNs is justified by previous studies, which found that different viewing angles were largely degenerate with the average values of 30 o and 70 o for Type I and II AGNs, respectively (e.g. Mountrichas et al 2021 ;Ramos Padilla et al 2022 ).…”
Section: Stellar Mass Estimationmentioning
confidence: 99%
“…We note that only two viewing angles are selected, in order to obtain the most informative parameters. Ramos Padilla et al (2022) have tested the effect of the viewing angles in AGN classification, and found that limiting the viewing angles representing these two types of AGNs (30°/70°) does not affect the estimated physical parameters (i.e., f AGN ) as compared to using the full range of viewing angles.…”
Section: Estimating the Agn Contribution And Sfr From Sed Fittingmentioning
confidence: 99%